2019
DOI: 10.1016/j.jsha.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-world use of ticagrelor versus clopidogrel in percutaneous coronary intervention-treated ST-elevation myocardial infarction patients: A single-center registry study

Abstract: ObjectivesThe primary aim was to investigate the efficacy and safety of dual antiplatelet therapy (DAPT) using ticagrelor (T-DAPT) versus clopidogrel (C-DAPT) in a real-world ST-elevation myocardial infarction (STEMI) population.MethodsWe retrospectively analyzed 655 consecutive patients having primary percutaneous coronary intervention (PCI) for STEMI at Liverpool Hospital, Sydney, Australia (from January 2013 to April 2016). Medical and procedural therapies were at clinician discretion. Patient data were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In addition, 111 full-text manuscripts were assessed for eligibility, and 82 of them were excluded as they did not meet the inclusion criteria. Therefore, only 29 studies involving 165,981 patients were included in the study [ 10 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [37] , [38] , [39] , [40] ]( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 111 full-text manuscripts were assessed for eligibility, and 82 of them were excluded as they did not meet the inclusion criteria. Therefore, only 29 studies involving 165,981 patients were included in the study [ 10 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [37] , [38] , [39] , [40] ]( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After adjustment, ticagrelor was associated with a lower risk of cardiovascular complications than clopidogrel. Three real-world studies on STEMI patients with PCI revealed that, compared with clopidogrel, ticagrelor improved 1-year survival [ 92 ], and was associated with lower adjusted 12-month mortality [ 93 ] and all-cause mortality rates [ 94 ].…”
Section: Clinical Researchmentioning
confidence: 99%